A new pimarane-type diterpenoid from moss Pseudoleskeella papillosa (Lindb.) Kindb - Na Liu; Song Wang; Hongxiang Lou (Elsevier, 2012)
A new pimarane-type diterpenoid, momilactone C (1), together with one known compound, momilactone A (2), was isolated from moss Pseudoleskeella papillosa by column chromatography on silica gel, Sephadex LH-20 and semi-preparative HPLC. Their structures were established on the basis of HR-ESI-MS, 1D and 2D NMR spectroscopic methods. Allelopathic test showed that the two diterpenoids inhibited germination of the Arabidopsis thaliana seeds.